Assessment of yield losses due to grain smut in barnyard millet - and H.S. YADAVA, A.K. JAIN, S.K. JAIN* (Indian Phytopathology, 2002)
An experiment was carried out in 2 consecutive years to estimate losses in grain yield due to grain smut (Ustilago panici-frumentacei) genotypes of barnyard millet (Echinochloa frumentacea) in Madhya Pradesh, India. Of the 13 tested genotypes, K 1 was resistant and showed minimum yield loss. The susceptible genotypes (RAU 10 and RAU 11) resulted in maximum yield loss. The mean grain yield loss varied between 6.5 and 60.8% in different genotypes. Both incidence and severity of the disease were significantly and positively correlated with losses in grain yield, but severity contributed more. The prediction models for estimating yield losses were derived by considering incidence and severity together or individually.